2022
DOI: 10.1371/journal.pone.0276153
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional ultrasound signs as predictive markers of massive peri-operative blood loss in placenta previa suspicious for placenta accreta spectrum (PAS) disorder

Abstract: Objective To evaluate certain two-dimensional (2D) ultrasound signs as predictors of massive peri-operative blood loss (PBL) in pregnant women with placenta previa suspicious of PAS disorder. Materials and methods A single center retrospective study was done in pregnant women who had undergone prenatal diagnosis with 2D ultrasound grey scale and color Doppler using the EW-AIP (which has been changed to IS-PAS (International Society for the Placenta Accreta Spectrum)) criteria between January 2007 and May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
(118 reference statements)
1
5
1
Order By: Relevance
“…Moreover, the median number of parities was 5 in the minor group and 6 in the major group with a significant difference between the two groups [p-value= 0.007]. This comes in agreement with Watthanasathitnukun et al [8] , where a significant difference was found [p-value <.001]. However, Zhou et al [9] did not find a significant difference.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Moreover, the median number of parities was 5 in the minor group and 6 in the major group with a significant difference between the two groups [p-value= 0.007]. This comes in agreement with Watthanasathitnukun et al [8] , where a significant difference was found [p-value <.001]. However, Zhou et al [9] did not find a significant difference.…”
Section: Discussionsupporting
confidence: 75%
“…However, the mean gestational age did not have a significant difference between the two groups [p-value= 0.6]. This comes in contrast with previous reports where a significant difference was found [7][8] . This may be attributed to different geographical area and inclusion criteria of the mentioned studies.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In this study we included only patients with complete placenta previa defined as: placenta previa completely covering cervical OS. All patients with complete placenta previa was evaluated by Ultrasound Scoring System before operation, and ultrasound score ≥ 6 points was identified as suspicious placenta accreta spectrum (PAS) disorder as previous published article, [15][16][17] and patients with suspicious PAS disorder were excluded from the study. All patients in this study were well planned and prepared before operation, elective cesarean section was scheduled between 36 and 38 weeks according to Clinical Practice Guideline.…”
Section: Patientsmentioning
confidence: 99%